A Hamster Antibody to the Mouse Fibrinogen Chain Inhibits Platelet-fibrinogen Interactions and FXIIIa-mediated Fibrin Cross-linking, and Facilitates Thrombolysis - JirouȈsková, Markéta; Smyth, Susan S.; Kudryk, Bohdan; Coller, Barry S. (Thrombosis and Haemostasis, 2001)
Murine models employing genetically altered mice have the potential to provide important new information about the hemostatic system, but before such data can be extrapolated to humans it is necessary to define the similarities and differences between murine and human hemostasis. After establishing the similarities of murine fibrinogen to human fibrinogen in its pattern of proteolysis in response to plasmin and its cross-linking by factor XIIIa, we studied a new hamster monoclonal antibody (mAb) 7E9 that reacts with the γ chain of mouse fibrinogen. This antibody inhibits platelet adhesion to fibrinogen, platelet-mediated clot retraction, platelet aggregation, and FXIIIa-mediated cross-linking of fibrin; it also facilitates tissue plasminogen activator (tPA)-mediated lysis of fibrin formed either in the absence or presence of platelets. These data provide evidence that the C-terminus of mouse fibrinogen γ chain, like that of human fibrinogen, is involved in fibrinogen binding to platelets and FXIIIa-mediated cross-linking of fibrin. Our data raise the possibility that a therapeutic agent that targets the C-terminus of the γ chain in human fibrinogen might have broad antithrombotic and profibrinolytic effects.
Keywords: Fibrinogen; thrombolysis; factor XIIIa; antithrombotic therapy